Modes of spread in social innovation: A social topology case in rural Portugal - Jamie-Scott Baxter (Journal of Rural Studies, 2023)
The potential of social innovation to address intersecting social and spatial inequalities in regional territories is increasingly recognised. Against this background, the results in this article are based on a qualitative study of constellations of actors in peripheral rural regions engaged in socially innovative approaches to regional development. Empirically, the example of EPAM — a network of new young farmers across Portugal — is investigated using social topology methodology to demonstrate how social innovation spreads through rural regions. Data were collected and analysed across spatial scales to examine how images circulate ecologies of infrastructure –including EPAM – and traverse territorial boundaries. In this way, images as specific material-discursive configurations are shown to be agential in the performative spreading of social innovation. To conceptualise these observations, the article is based on the assumption that social innovation has dual spatial properties. The first, an empirically legible and bounded object moving in space (regional). The second, an trans-scalar relational process in which objects, subjects, and spaces are reciprocally reconfigured (process-relational). This assumption has implications on understanding diffusion dynamics in social innovation, specifically how does social innovation spread in a process-relational mode? Against this background, the primary aim of the article is to examine and elaborate the diffusion dynamics of social innovation in its process-relational mode in the case of EPAM. Applying social topology methodology with agential realist theoretical sensitivity is well suited to theoretically elaborate modes of spread in social innovation according to their spatial properties.
Keywords: 630; Social innovation; Space; Diffusion; Peripheral rural regions; Topology; Agential realism; Process-relational